Plaster, Render, Paint and Coatings : Details, Products, Case Studies - Reichel, Alexander (Birkhäuser, 2012)
Plastering, colors, and coatings help characterize surfaces, determine the impression a room makes, create light effects. This volume uses international examples to present innovative solutions on this theme. Expert authors describe and define the essential principles, drawing attention to points to be aware of.